Copper in-situ reinforced multilayer oxygen barrier impact-resistant ceramic tile body and ceramic tile and preparation method thereof
Patent Information
- Application Number
- CN202611425940.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-27
AI Technical Summary
然而,建筑陶瓷作为一类典型的脆性材料,其抗冲击性能不足,在日常使用过程中易受到重物撞击而破碎,不仅更换、维护成本较高,且应用于台面、墙面等场景中还存在一定的安全隐患
(1)首次将金属铜粉均匀分散于坯体中间层的粉料中,并通过一次高温烧成(测温环温度≥1130℃,高于金属铜的熔点1083 ℃)使铜粉熔融并相互连接,形成连续的三维网状金属增韧层,借助铜的高韧性、高塑性和延展性,有效阻滞裂纹扩展,大幅提升砖体的抗冲击能力。(2)通过合理的多层坯体结构设计(普通粉料层-高铝粉料层-高韧性粉料层-高铝粉料层-普通粉料层的层合结构),利用上下普通粉料层和高铝粉料层的致密化烧结,在烧成过程中隔绝外部氧气向坯体内部扩散,从而保护铜粉在高温下不被氧化,避免因生成氧化铜而丧失金属增韧效果;同时,高铝粉料层中高铝低钾钠的配方设计,可中和少量被氧化的铜粉(即在金属铜部分氧化产物—氧化铜的作用下,高温层可进行有效烧结,不至于发生过烧),防止坯体产生鼓包缺陷。(3)由于金属铜的热膨胀系数(16×10-6 K-1~ 17×10-6K-1)远大于建筑陶瓷坯体的热膨胀系数(通常为7×10-6 K-1~ 10×10-6 K-1),所以铜-陶瓷复合层(高韧性粉料层)的热膨胀系数大于高铝粉料层与普通粉料层,由此由于高韧性粉料层和高铝粉料层、普通粉料层在高温烧成后降温过程的热失配,可在建筑陶瓷表面有效引入残余压应力,继而可抵消外载引入的拉应力、抑制表面裂纹的萌生与扩展,继而可有效提升建筑陶瓷的抗冲击性能。
Smart Images

Figure CN122977828A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building ceramics, specifically to a green body for a multi-layer oxygen-barrier impact-resistant ceramic brick based on in-situ copper reinforcement, as well as the ceramic brick and its preparation method. Background Technology
[0002] Ceramic tiles are widely used in flooring, interior and exterior wall decoration due to their excellent properties such as wear resistance, corrosion resistance, and ease of cleaning, and their application scope and fields are expanding daily. However, as a typical brittle material, building ceramics have insufficient impact resistance and are easily broken by heavy objects during daily use. This not only results in high replacement and maintenance costs but also poses certain safety hazards when used for countertops, walls, and other applications. For a long time, how to effectively improve the impact resistance of building ceramic tiles while maintaining their original decorative properties has been a pressing technical challenge for the industry. Summary of the Invention
[0003] To address the problems raised in this background technology, the purpose of this invention is to introduce highly ductile copper metal into the green body, utilize the excellent plastic deformation capacity of the copper-ceramic composite to absorb impact energy, and at the same time utilize the residual stress of thermal mismatch between the copper-ceramic composite layer and the green body layer to improve the impact resistance of building ceramic products.
[0004] In a first aspect, the present invention provides a green body for multilayer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement. The blank has a multi-layer structure, including a common powder layer, a high-alumina powder layer, a high-toughness powder layer, another high-alumina powder layer, and a common powder layer arranged sequentially. The chemical composition of the high-alumina powder includes, by mass percentage: SiO2: 50%~60%; Al2O3: 30%~40%; Fe2O3: 0.5%~1.5%; TiO2: 0.1%~0.8%; CaO: 0.1%~0.5%; MgO: 0.2%~1.5%; K2O: 1%~3%; Na2O: 1%~2%; loss on ignition: 3%~8%. The raw material composition of the high-toughness powder includes, based on a total of 100 parts by weight of high-alumina powder and copper powder: 40~70 parts of high-alumina powder and 30~60 parts of copper powder. The thickness ratio of the common powder layer, the high-alumina powder layer, and the high-toughness powder layer is 5~12:1:1~4. The thickness of the ordinary powder layer here refers to the thickness of a single ordinary powder layer, not the sum of the thicknesses of two ordinary powder layers. Similarly, the thickness of the high-alumina powder layer here refers to the thickness of a single high-alumina powder layer, not the sum of the thicknesses of two high-alumina powder layers.
[0005] In an optional embodiment, the mineral composition of the high-alumina powder includes, by mass percentage: 5%~16% sodium sand, 10%~20% potassium aluminum sand, 8%~15% high white potassium sand, 18%~45% clay, 1%~4% bentonite, 1%~4% talc, 20%~40% high alumina stone, and 2%~6% waste porcelain powder.
[0006] In an optional embodiment, the chemical composition of the ordinary powder includes, by mass percentage: SiO2: 60%~68%; Al2O3: 20%~25%; Fe2O3: 0.4%~1.0%; TiO2: 0.2%~0.4%; CaO: 0.1%~0.6%; MgO: 0.2%~1.2%; K2O: 1.5%~5%; Na2O: 1.5%~4%; Loss on ignition: 3%~8%.
[0007] In an optional embodiment, the mineral composition of the ordinary powder includes, by mass percentage: 19%~32% sodium sand, 15%~30% potassium aluminum sand, 10%~20% high white potassium sand, 18%~41% clay, 1%~4% bentonite, 1%~4% talc, 2%~8% high aluminum stone, and 1%~6% waste porcelain powder.
[0008] In an optional embodiment, the coefficient of thermal expansion of the ordinary powder layer at 40~600℃ is 8.0×10⁻⁶. -6 K -1 ×9.5×10 -6 K -1 The coefficient of thermal expansion of the high-alumina powder layer at 40~600℃ is 6.5×10⁻⁶. -6 K -1 ~ 8.0×10 -6 K -1 The high-toughness powder layer has a coefficient of thermal expansion of 9.2 × 10⁻⁶ at 40–600℃. -6 K -1 ~ 12.8×10 -6 K -1 .
[0009] In an optional embodiment, the thickness of the ordinary powder layer is 3-6 mm, the thickness of the high-alumina powder layer is 0.5-1 mm, and the thickness of the high-toughness powder layer is 1-2 mm. Here, the thickness of the ordinary powder layer refers to the thickness of a single ordinary powder layer, not the sum of the thicknesses of two ordinary powder layers. Similarly, the thickness of the high-alumina powder layer refers to the thickness of a single high-alumina powder layer, not the sum of the thicknesses of two high-alumina powder layers.
[0010] Secondly, the present invention provides a multi-layer oxygen-barrier impact-resistant ceramic tile based on copper in-situ reinforcement. The multi-layer oxygen-barrier impact-resistant ceramic tile based on copper in-situ reinforcement includes the aforementioned green body for the multi-layer oxygen-barrier impact-resistant ceramic tile based on copper in-situ reinforcement.
[0011] Thirdly, this invention provides a method for preparing multilayer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement. The preparation method includes the following steps: Step (1) The ordinary powder, high alumina powder, high toughness powder, high alumina powder and ordinary powder are applied in sequence, and then the blank is obtained by pressing. Step (2) Apply a surface glaze to the dried body surface; Step (3) Print a pattern in ordinary ink on the surface of the glazed body by inkjet printing; Step (4) Apply a protective glaze to the surface of the blank after inkjet printing a pattern with ordinary ink; Step (5) Fire the green body after applying the protective glaze to obtain a multi-layer oxygen-barrier impact-resistant ceramic brick based on in-situ copper reinforcement.
[0012] In an optional implementation, in step (1), first apply 6-12 kg of ordinary powder per square meter, then apply 1-2 kg of high-alumina powder per square meter, then apply 2-4 kg of high-toughness powder per square meter, then apply 1-2 kg of high-alumina powder per square meter, and finally apply 6-12 kg of ordinary powder per square meter.
[0013] In an optional embodiment, in step (5), the firing temperature is 1130~1180℃ and the firing cycle is 40~60 minutes.
[0014] In an optional embodiment, in step (2), the chemical composition of the glaze includes, by mass percentage: SiO2: 60%~70%; Al2O3: 15%~25%; Fe2O3: 0.1%~0.5%; TiO2: 0.1%~0.5%; CaO: 0.1%~0.5%; MgO: 1%~5%; K2O: 2%~6%; Na2O: 2%~4%; ZrO2: 3%~10%; loss on ignition: 1%~3%.
[0015] In an optional embodiment, in step (2), the mineral composition of the glaze includes, by mass percentage, 25%~35% potassium feldspar, 15%~30% sodium feldspar, 12%~18% kaolin, 12%~18% quartz sand, 8%~12% zirconium silicate, 1%~5% alumina, 2%~4% calcined talc, and 3%~8% calcined kaolin.
[0016] In an optional embodiment, in step (2), the surface glaze is applied by spraying or pouring, with a specific gravity of 1.4~1.5 g / cm³. 3 The weight is 450~650 g / m 2 .
[0017] In an optional embodiment, in step (4), the chemical composition of the protective glaze includes, by mass percentage: SiO2: 45%~55%; Al2O3: 17%~24%; MgO: 1%~3%; CaO: 2%~6%; BaO: 3%~8%; ZnO: 2.5%~5%; K2O: 1%~3%; Na2O: 3.5%~5%; loss on ignition: 4%~9%.
[0018] In an optional embodiment, in step (4), the mineral composition of the protective glaze includes, by mass percentage: 10%~20% potassium feldspar, 35%~45% sodium feldspar, 10%~20% kaolin, 3%~5% zinc oxide, 5%~10% calcite, 3%~6% calcined talc, 5%~10% barium carbonate, 2%~4% alumina, and 3%~6% calcined kaolin.
[0019] In an optional embodiment, in step (4), the protective glaze is applied by spraying, with a specific gravity of 1.35~1.40 g / cm³. 3 The glaze application rate is 250~300 g / m². 2 .
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) For the first time, metallic copper powder is evenly dispersed in the powder of the middle layer of the green body, and the copper powder is melted and connected to each other through a high-temperature firing (temperature of the measuring ring ≥1130℃, which is higher than the melting point of metallic copper 1083℃) to form a continuous three-dimensional network metal toughening layer. With the help of the high toughness, high plasticity and ductility of copper, crack propagation is effectively inhibited and the impact resistance of the brick is greatly improved. (2) Through a reasonable multi-layered green body structure design (a laminated structure of ordinary powder layer - high alumina powder layer - high toughness powder layer - high alumina powder layer - ordinary powder layer), the densification sintering of the upper and lower ordinary powder layers and high alumina powder layers is used to isolate external oxygen from diffusing into the green body during the firing process, thereby protecting the copper powder from oxidation at high temperatures and avoiding the loss of metal toughening effect due to the formation of copper oxide; at the same time, the high alumina and low potassium sodium formulation design in the high alumina powder layer can neutralize a small amount of oxidized copper powder (that is, under the action of copper oxide, a partial oxidation product of metallic copper, the high temperature layer can be effectively sintered without over-burning), preventing the green body from producing bulging defects. (3) Due to the thermal expansion coefficient of metallic copper (16×10), -6 K -1 ~ 17×10 -6 K -1 The coefficient of thermal expansion is much greater than that of building ceramic bodies (usually 7×10). -6 K -1 ~ 10×10 -6 K -1Therefore, the coefficient of thermal expansion of the copper-ceramic composite layer (high-toughness powder layer) is greater than that of the high-alumina powder layer and the ordinary powder layer. As a result, due to the thermal mismatch between the high-toughness powder layer, the high-alumina powder layer, and the ordinary powder layer during the cooling process after high-temperature firing, residual compressive stress can be effectively introduced into the surface of the building ceramics. This can then offset the tensile stress introduced by the external load, inhibit the initiation and propagation of surface cracks, and thus effectively improve the impact resistance of the building ceramics. Attached Figure Description
[0021] Figure 1 This is a cross-sectional view of the impact-resistant ceramic in Example 1. Detailed Implementation
[0022] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention. The following exemplary description illustrates the green body for multilayer oxygen-barrier impact-resistant ceramic bricks based on copper in-situ reinforcement, the ceramics thereon, and the method for preparing the ceramics.
[0023] The blank has a multi-layer structure, including a common powder layer, a high-alumina powder layer, a high-toughness powder layer, a high-alumina powder layer, and a common powder layer arranged in sequence.
[0024] In an optional embodiment, the chemical composition of the ordinary powder may include, by mass percentage: SiO2: 60%~68%; Al2O3: 20%~25%; Fe2O3: 0.4%~1.0%; TiO2: 0.2%~0.4%; CaO: 0.1%~0.6%; MgO: 0.2%~1.2%; K2O: 1.5%~5%; Na2O: 1.5%~4%; Loss on ignition: 3%~8%.
[0025] It should be understood that any common powder mineral composition that causes the chemical composition of the common powder to fall within the above range is applicable to the present invention. For example, the mineral composition of the common powder includes, by mass percentage: 19%~32% sodium sand, 15%~30% potassium aluminum sand, 10%~20% high white potassium sand, 18%~41% clay, 1%~4% bentonite, 1%~4% talc, 2%~8% high aluminum stone, and 1%~6% waste porcelain powder.
[0026] The chemical composition of sodium sand includes, by mass percentage: SiO2: 65%~75%; Al2O3: 15%~20%; Fe2O3: 0.1%~1%; TiO2: 0.1%~1%; CaO: 0.5%~1%; MgO: 0.1%~1%; K2O: 1%~5%; Na2O: 4%~10%; Loss on ignition: 1%~5%. For example, the chemical composition of sodium sand used in the examples and comparative examples includes, by mass percentage: SiO2: 71.19%, Al2O3: 17.67%, Fe2O3: 0.52%, TiO2: 0.15%, CaO: 0.66%, MgO: 0.22%, K2O: 1.89%, Na2O: 5.37%, Loss on ignition: 2.33%.
[0027] The chemical composition of potassium aluminum sand may include, by mass percentage: SiO2: 60%~70%; Al2O3: 20%~30%; Fe2O3: 0.5%~2%; TiO2: 0.1%~1%; CaO: 0.1%~1%; MgO: 0.1%~1%; K2O: 1%~5%; Na2O: 1%~5%; Loss on ignition: 4%~6%. For example, the chemical composition of potassium aluminum sand used in the examples and comparative examples may include, by mass percentage: SiO2: 64.59%, Al2O3: 23.17%, Fe2O3: 0.96%, TiO2: 0.16%, CaO: 0.45%, MgO: 0.20%, K2O: 2.81%, Na2O: 2.37%, Loss on ignition: 5.29%.
[0028] The chemical composition of high-white potassium sand may include, by mass percentage: SiO2: 65%~75%; Al2O3: 15%~20%; Fe2O3: 0.5%~1%; TiO2: 0.01%~0.2%; CaO: 0.01%~0.2%; MgO: 0.01%~0.5%; K2O: 4%~8%; Na2O: 0.2%~1%; Loss on ignition: 3%~5%. For example, the chemical composition of the high-white potassium sand specifically used in the examples and comparative examples may include, by mass percentage: SiO2: 69.95%, Al2O3: 18.51%, Fe2O3: 0.61%, TiO2: 0.09%, CaO: 0.07%, MgO: 0.10%, K2O: 6.14%, Na2O: 0.51%, Loss on ignition: 4.02%. The whiteness of high-white potassium sand after ignition is above 80 degrees.
[0029] The chemical composition of the high-alumina alumina includes, by mass percentage: SiO2: 35%~45%; Al2O3: 50%~55%; Fe2O3: 1%~2%; TiO2: 1%~2%; CaO: 0.5%~1%; MgO: 0.1%~1%; K2O: 0.2%~0.6%; Na2O: 0.1%~0.5%; Loss on ignition: 1%~5%. For example, the chemical composition of the high-alumina alumina specifically used in the examples and comparative examples includes, by mass percentage: SiO2: 39.66%, Al2O3: 53.33%, Fe2O3: 1.75%, TiO2: 1.85%, CaO: 0.92%, MgO: 0.35%, K2O: 0.41%, Na2O: 0.13%, Loss on ignition: 1.60%.
[0030] The chemical composition of waste porcelain powder may include, by mass percentage: SiO2: 70%~80%; Al2O3: 15%~20%; Fe2O3: 1%~2%; TiO2: 0.1%~1%; CaO: 0.5%~2%; MgO: 1%~2%; K2O: 2%~3%; Na2O: 2%~4%; Loss on ignition: 0.1%~1%. For example, the chemical composition of the waste porcelain powder specifically used in the examples and comparative examples may include, by mass percentage: SiO2: 73.07%, Al2O3: 18.11%, Fe2O3: 1.01%, TiO2: 0.28%, CaO: 0.68%, MgO: 1.01%, K2O: 2.61%, Na2O: 2.89%, Loss on ignition: 0.34%.
[0031] In an optional embodiment, the coefficient of thermal expansion of the ordinary powder layer at 40~600℃ is 8.0×10⁻⁶. -6 K -1 ~ 9.5×10 -6 K -1 .
[0032] Weigh the raw materials according to the mineral composition of ordinary powder, mix them evenly with additives and water to prepare ordinary powder slurry, ball mill, sieve, age, and then spray granulate. As an example, the raw material composition of the ordinary powder slurry includes: by mass percentage, 65.59% dry ordinary powder, 0.15% sodium tripolyphosphate, 0.30% diluent, 0.8% water glass, and 33.06% water. The mass residue of the ordinary powder slurry passing through a 250-mesh sieve is ≤1.2%.
[0033] The chemical composition of high-alumina powder may include, by mass percentage: SiO2: 50%~60%; Al2O3: 30%~40%; Fe2O3: 0.5%~1.5%; TiO2: 0.1%~0.8%; CaO: 0.1%~0.5%; MgO: 0.2%~1.5%; K2O: 1%~3%; Na2O: 1%~2%; Loss on ignition: 3%~8%.
[0034] It should be understood that any high-alumina powder mineral composition that causes the chemical composition of the high-alumina powder to fall within the above range is applicable to this invention. The mineral composition of the high-alumina powder includes, by mass percentage: 5%~16% sodium sand, 10%~20% potassium aluminum sand, 8%~15% high-white potassium sand, 18%~45% clay, 1%~4% bentonite, 1%~4% talc, 20%~40% high-alumina stone, and 2%~6% waste porcelain powder.
[0035] The coefficient of thermal expansion of the high-alumina powder layer is 6.5 × 10⁻⁶ at 40–600 °C. -6 K -1 ~ 8.0×10 -6 K -1 In an optional embodiment, the coefficient of thermal expansion of the ordinary powder layer is higher than that of the high-alumina powder layer (1~1.5)×10⁻⁶. -6 K -1 .
[0036] According to the mineral composition of the high-alumina powder, each raw material is weighed and mixed evenly with additives and water to prepare a high-alumina powder slurry. This slurry is then ball-milled, sieved, aged, and spray-granulated. As an example, the raw material composition of the high-alumina powder slurry includes, by mass percentage: 66.11% dry high-alumina powder, 0.15% sodium tripolyphosphate, 0.30% diluent, 0.8% water glass, and 32.64% water. The mass residue of the high-alumina powder slurry passing through a 250-mesh sieve is ≤1.2%.
[0037] The raw material composition of the high-toughness powder includes: 40-70 parts high-alumina powder and 30-60 parts copper powder, totaling 100 parts by weight. After uniform mixing of the high-alumina powder slurry and copper powder, the mixture is spray-granulated. Excessive copper powder leads to sedimentation and makes spray granulation difficult. Insufficient copper powder results in the copper powder melting and remaining independent during firing, failing to bond together and leading to insufficient toughness in the high-toughness powder layer, thus failing to improve impact resistance.
[0038] The preferred copper powder is 200-300 mesh. Coarser copper powder is prone to sedimentation and significantly affects powder coating. Too fine a copper powder is too easily oxidized during powder preparation. Oxidized copper powder forms copper oxide, which reacts with ordinary powder as a flux, forming a large amount of low-temperature glassy material. This affects the venting of the green body and leads to bulging defects.
[0039] The high-alumina powder adopts a high-alumina, low-potassium sodium formula mainly to neutralize the formed copper oxide and prevent the formation of bulges in the green body. The role of copper powder: (1) The metallic copper powder is uniformly dispersed in the high-toughness powder of the green body. Through a high-temperature firing (temperature of the measuring ring ≥ 1130℃, which is higher than the melting point of metallic copper 1083℃), the copper powder melts and connects with each other to form a continuous three-dimensional network metal toughening layer. With the help of the high toughness, high plasticity and ductility of copper, it effectively inhibits the expansion of cracks and greatly improves the impact resistance of the brick. (2) Due to the thermal expansion coefficient of metallic copper (16×10⁻⁶), -6 K -1 ~ 17×10 -6 K -1 The coefficient of thermal expansion is much greater than that of ordinary green body powder (usually 7×10). -6 K -1 ~ 10×10 -6 K -1 Therefore, the coefficient of thermal expansion of the copper-ceramic composite layer (high-temperature toughness layer) is greater than that of the high-alumina powder layer and the ordinary powder layer. As a result, due to the thermal mismatch between the high-temperature toughness layer and the high-alumina powder layer and the ordinary powder layer during the cooling process after high-temperature firing, residual compressive stress can be effectively introduced into the surface of the building ceramics. This can then offset the tensile stress introduced by the external load, inhibit the initiation and propagation of surface cracks, and thus effectively improve the impact resistance of the building ceramics.
[0040] A green body is obtained by layering and shaping multiple layers of powder. The powder layering sequence can be as follows: first, apply 6-12 kg of ordinary powder per square meter; then, apply 1-2 kg of high-alumina powder per square meter; next, apply 2-4 kg of high-toughness powder per square meter; then, apply 1-2 kg of high-alumina powder per square meter; and finally, apply 6-12 kg of ordinary powder per square meter. The green body is then formed using a press. The green body is then dried, which can be done in a drying kiln.
[0041] In an optional embodiment, the thickness ratio of the ordinary powder layer, the high-alumina powder layer, and the high-toughness powder layer is 5~12:1:1~4. For example, the thickness ratio of the ordinary powder layer, the high-alumina powder layer, and the high-toughness powder layer is 5:1:2.
[0042] Through a rational multi-layered green body structure design (a laminated structure of ordinary powder layer - high alumina powder layer - high toughness powder layer - high alumina powder layer - ordinary powder layer), the densification sintering of the upper and lower ordinary powder layers and high alumina powder layers isolates most of the external oxygen from diffusing into the green body during the firing process, thereby protecting most of the copper powder from oxidation at high temperatures and avoiding the loss of metal toughening effect due to the generation of a large amount of copper oxide; at the same time, the high alumina and low potassium sodium formulation design in the high alumina powder layer can neutralize a small amount of oxidized copper powder (that is, under the action of copper oxide, a product of partial oxidation of metallic copper, the high-temperature layer can be effectively sintered without over-burning), preventing the green body from developing bulging defects.
[0043] Dry the green body. Apply a top glaze to the dried green body. The chemical composition of the top glaze may include, by mass percentage: SiO2: 60%~70%; Al2O3: 15%~25%; Fe2O3: 0.1%~0.5%; TiO2: 0.1%~0.5%; CaO: 0.1%~0.5%; MgO: 1%~5%; K2O: 2%~6%; Na2O: 2%~4%; ZrO2: 3%~10%; Loss on ignition: 1%~3%.
[0044] As an example, the mineral composition of the glaze includes, by mass percentage: 25%~35% potassium feldspar, 15%~30% sodium feldspar, 12%~18% kaolin, 12%~18% quartz sand, 8%~12% zirconium silicate, 1%~5% alumina, 2%~4% calcined talc, and 3%~8% calcined kaolin.
[0045] Preparation of the glaze slurry: Weigh the raw materials according to the mineral composition of the glaze, mix them evenly with additives and water, and then sieve to obtain the glaze slurry. The additives include sodium carboxymethyl cellulose and sodium tripolyphosphate. As an example, the mass content of sodium carboxymethyl cellulose in the glaze mineral composition is 0.1%~0.5%, and the mass content of sodium tripolyphosphate is 0.1%~0.5%. Water can be added to the glaze slurry before glazing to adjust to the desired specific gravity. The glaze is applied by spraying or pouring, with a specific gravity of 1.4~1.5 g / cm³. 3 The weight is 450~650 g / m 2 .
[0046] Ordinary ink patterns are printed on the surface of the blank after the surface glaze is applied. The texture and color of the ink pattern can be adjusted to adapt to the layout design.
[0047] A protective glaze is applied to the surface of the blank after inkjet printing a pattern using ordinary ink. The chemical composition of the protective glaze may include, by mass percentage: SiO2: 45%~55%; Al2O3: 17%~24%; MgO: 1%~3%; CaO: 2%~6%; BaO: 3%~8%; ZnO: 2.5%~5%; K2O: 1%~3%; Na2O: 3.5%~5%; Loss on ignition: 4%~9%.
[0048] For example, the mineral composition of the protective glaze includes, by mass percentage: 10%~20% potassium feldspar, 35%~45% sodium feldspar, 10%~20% kaolin, 3%~5% zinc oxide, 5%~10% calcite, 3%~6% calcined talc, 5%~10% barium carbonate, 2%~4% alumina, and 3%~6% calcined kaolin.
[0049] Prepare a protective glaze slurry. Weigh the raw materials according to the mineral composition of the protective glaze, mix them evenly with additives and water, and then sieve to obtain the protective glaze slurry. The additives include sodium carboxymethyl cellulose and sodium tripolyphosphate. As an example, the mass content of sodium carboxymethyl cellulose in the protective glaze mineral composition is 0.1%~0.5%, and the mass content of sodium tripolyphosphate in the protective glaze mineral composition is 0.1%~0.5%. Water can be added to the protective glaze slurry before glazing to adjust to the desired specific gravity. The protective glaze is applied by spraying. In an optional embodiment, the specific gravity of the protective glaze is 1.35~1.40 g / cm³. 3 The glaze application rate is 250~300g / m². 2 .
[0050] Firing. The kiln firing temperature (ring temperature) is 1130~1180℃, and the firing cycle is 40~60 minutes. In the ceramics industry, the ring temperature (RT) refers to the equivalent temperature value calculated from the physical shrinkage of the ring during firing. It is used to quantify the overall thermal effect experienced by the product in the kiln. The actual temperature inside the kiln is usually about 40℃ higher than the ring temperature.
[0051] Edge grinding and grading.
[0052] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0053] Implementation Column 1 The preparation method of multilayer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement includes the following steps: Step 1: Prepare the common powder according to the formula. The mineral composition of the common powder includes, by mass percentage: sodium sand 31%, potassium aluminum sand 18.7%, high-white potassium sand 11%, clay 27.5%, bentonite 2%, talc 2.3%, high-alumina stone 4%, and waste porcelain powder 3.5%. The chemical composition of the common powder includes, by mass percentage: SiO2: 64.53%, Al2O3: 23.24%, Fe2O3: 0.78%, TiO2: 0.29%, CaO: 0.35%, MgO: 0.82%, K2O: 2.21%, Na2O: 2.54%. Loss on ignition: 5.24%.
[0054] Step 2: Prepare high-alumina powder according to the formula. The mineral composition of the high-alumina powder includes, by mass percentage: sodium sand 9%, potassium aluminum sand 18.5%, high-white potassium sand 11%, clay 27.5%, bentonite 2%, talc 2.3%, high-alumina stone 26%, and waste porcelain powder 3.7%. The chemical composition of the high-alumina powder includes, by mass percentage: SiO2: 57.38%, Al2O3: 31.26%, Fe2O3: 1.08%, TiO2: 0.65%, CaO: 0.44%, MgO: 0.83%, K2O: 2.11%, Na2O: 1.05%, and loss on ignition 5.20%.
[0055] Step 3: Prepare the high-toughness powder according to the formula. After the high-alumina powder slurry and copper powder are mixed evenly, a high-toughness slurry is prepared and spray-granulated. The copper powder has a mesh size of 200 mesh. The raw material composition of the high-toughness powder includes: 50 parts of high-alumina powder and 50 parts of copper powder, based on a total weight of 100 parts.
[0056] Step 4: Applying and pressing the blank. The order of applying the powder to the blank is as follows: 7.5 kg / m² of ordinary powder, then 1.5 kg / m² of high-alumina powder, then 3 kg / m² of high-toughness powder, then another 1.5 kg / m² of high-alumina powder, and finally 7.5 kg / m² of ordinary powder. After applying the powder, press the blank and dry it. The coefficient of thermal expansion of the ordinary powder layer is 8.3 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of the high-alumina powder layer is 7.1 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of the high-toughness powder layer is 11.35 × 10⁻⁶. -6 K -1 The thickness of the (single-layer) ordinary powder layer is 3.8 mm, the thickness of the (single-layer) high-alumina powder layer is 0.75 mm, and the thickness of the high-toughness powder layer is 1.5 mm.
[0057] Step 5: Dry the green body and apply a top glaze to its surface. The mineral composition of the top glaze includes, by mass percentage: 31% potassium feldspar, 20% sodium feldspar, 15% kaolin, 15% silicate sand, 10% zirconium silicate, 2% alumina, 3% calcined talc, and 4% calcined kaolin. The chemical composition of the top glaze includes, by mass percentage: 65.63% SiO2, 18.00% Al2O3, 0.15% Fe2O3, 0.14% TiO2, 0.27% CaO, 1.09% MgO, 3.51% K2O, 3.04% Na2O, 6.37% ZrO2, and a loss on ignition of 1.80%. The top glaze is applied by spraying, with a specific gravity of 1.45 g / cm³. 3 Glazing amount 500 g / m 2 .
[0058] Step 6: Print a regular ink pattern on the surface of the blank after applying the glaze.
[0059] Step 7: Apply a protective glaze to the surface of the blank after inkjet printing the pattern with ordinary ink. The mineral composition of the protective glaze includes, by mass percentage: 15% potassium feldspar, 40% sodium feldspar, 15% kaolin, 3% zinc oxide, 6% calcite, 4% calcined talc, 9% barium carbonate, 3% alumina, and 5% calcined kaolin. The chemical composition of the protective glaze includes, by mass percentage: 52.49% SiO2; 19.86% Al2O3; 1.54% MgO; 3.46% CaO; 7.01% BaO; 2.98% ZnO; 1.96% K2O; 4.36% Na2O; and a loss on ignition of 6.34%. The protective glaze is applied by spraying. The specific gravity of the protective glaze is 1.35 g / cm³. 3 Glazing amount is 280 g / m 2 .
[0060] Step 8: Firing the body after applying the protective glaze. The kiln firing temperature is 1150℃ (temperature of the measuring ring), and the firing cycle is 50 minutes.
[0061] Referring to the stepped drop height-critical cracking height method, the impact resistance was tested using a falling ball impact tester. A 50-gram steel ball was used in the falling ball impact test. The impact-resistant ceramic tile prepared in this example cracked at a height of 100 cm. The impact toughness was tested using GB / T14389-1993, the test method for impact toughness of engineering ceramics. The impact toughness of the impact-resistant ceramic tile prepared in this example was 3.61 kJ / m. 2 .
[0062] Figure 1This is a cross-sectional view of the impact-resistant ceramic from Example 1. The middle layer is a high-toughness powder layer, which is red in color. The metallic copper is red, while the copper oxide is black or green. This indicates that most of the copper powder is not oxidized.
[0063] Comparative Example 1 The method is essentially the same as Example 1, except that only ordinary powder is used, and the total weight of the powder is the same as in Example 1. Following the stepped drop height-critical cracking height method, the impact resistance was tested using a falling ball impact tester. A 50-gram steel ball was used for the falling ball impact test. The ceramic tile prepared in this comparative example cracked at a height of 60 cm. The impact toughness was tested using GB / T14389-1993, the test method for impact toughness of engineering ceramics. The impact toughness of the ceramic tile prepared in this comparative example was 1.96 kJ / m. 2 .
[0064] Comparative Example 2 The process is essentially the same as in Example 1, except that: 3 kg of ordinary powder is applied per square meter, followed by 1.5 kg of high-alumina powder per square meter, then 3 kg of high-toughness powder per square meter, then another 1.5 kg of high-alumina powder per square meter, and finally 3 kg of ordinary powder per square meter. Because the ordinary powder layer is relatively thin, a large amount of oxygen enters the interior of the green body. The high-alumina powder layer cannot completely consume the oxygen, resulting in a large amount of copper powder in the high-toughness powder layer being oxidized during firing. The large amount of copper oxide exceeds the neutralizing effect of the high-alumina powder layer, significantly increasing the glass phase in the middle of the green body, leading to poor venting and causing bulging.
[0065] Comparative Example 3 The process is basically the same as in Example 1, except that the high-toughness powder layer is entirely made of 200-mesh copper powder. When pressing the blank after the material is applied, there will be obvious delamination, and it is impossible to press a complete blank. This is because: (1) The high-toughness powder layer is entirely composed of copper powder, and copper powder has no adhesiveness and is not easy to press into a whole with ordinary powder. (2) The fineness of copper powder makes it difficult for the blank to release air during the pressing process, which also easily leads to delamination of the blank.
[0066] Comparative Example 4 The results are essentially the same as in Example 1, except that the raw material composition of the high-toughness powder includes 83 parts of high-alumina powder and 17 parts of copper powder, totaling 100 parts by weight. Following the stepped drop height-critical cracking height method, the impact resistance was tested using a falling ball impact tester with a 50-gram steel ball. The ceramic tile prepared in this comparative example cracked at a height of 60 cm. The impact toughness was tested using GB / T 14389-1993, the "Test Method for Impact Toughness of Engineering Ceramics," and the impact toughness of the ceramic tile prepared in this comparative example was 1.98 kJ / m. 2 Its impact toughness is close to that of ordinary bricks. This is because there is too little copper powder, and it is not connected into sheets in the body, so it cannot improve the impact resistance of the body.
[0067] Comparative Example 5 The process is essentially the same as in Example 1, except that: 9 kg of ordinary powder is applied per square meter, followed by 3 kg of high-toughness powder per square meter, and finally 9 kg of ordinary powder per square meter. Because the ordinary powder layer cannot completely isolate oxygen during firing, some copper powder in the high-toughness layer will be oxidized to copper oxide. When copper oxide comes into contact with the ordinary powder, it acts as a strong flux, causing the ordinary powder to overheat and resulting in bulging of the green body.
[0068] Comparative Example 6 The process is essentially the same as in Example 1, with the only difference being that the mineral composition of the high-alumina powder includes, by mass percentage: sodium sand 9%, potassium aluminum sand 18.5%, high-white potassium sand 11%, clay 27.5%, bentonite 2%, talc 2.3%, quartz powder 26%, and waste porcelain powder 3.7%. The chemical composition of the high-alumina powder includes, by mass percentage: SiO2: 72.88%, Al2O3: 17.65%, Fe2O3: 0.59%, TiO2: 0.23%, CaO: 0.25%, MgO: 0.76%, K2O: 1.78%, Na2O: 1.20%, with a loss on ignition of 4.66%. This high-alumina powder layer is a high-silicon, low-potassium sodium formulation. This formulation easily forms a large amount of glassy phase when in contact with copper oxide, leading to poor venting of the billet and potentially causing slight bulging.
[0069] Implement column 2 A method for preparing multilayer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement includes the following steps: Step 1: Prepare the common powder according to the formula. The mineral composition of the common powder includes, by mass percentage: sodium sand 20%, potassium aluminum sand 15%, high-white potassium sand 18%, clay 35%, bentonite 3%, talc 3%, high-alumina stone 2%, and waste porcelain powder 4%. The chemical composition of the common powder includes, by mass percentage: SiO2: 63.28%, Al2O3: 23.16%, Fe2O3: 0.81%, TiO2: 0.28%, CaO: 0.29%, MgO: 0.97%, K2O: 2.52%, Na2O: 2.78%. Loss on ignition: 5.91%.
[0070] Step 2: Prepare high-alumina powder according to the formula. The mineral composition of the high-alumina powder includes, by mass percentage: sodium sand 15%, potassium aluminum sand 15%, high-white potassium sand 8%, clay 25.5%, bentonite 2%, talc 2%, high-alumina stone 30%, and waste porcelain powder 2.5%. The chemical composition of the high-alumina powder includes, by mass percentage: SiO2: 57.13%, Al2O3: 31.90%, Fe2O3: 1.10%, TiO2: 0.71%, CaO: 0.47%, MgO: 0.75%, K2O: 1.77%, Na2O: 1.41%, with a loss on ignition of 4.76%.
[0071] Step 3: Prepare high-toughness powder according to the formula. Prepare a high-toughness slurry by mixing high-alumina powder slurry with copper powder, then spray granulate after uniform mixing. The copper powder has a mesh size of 200 mesh. The raw material composition of the high-toughness powder includes: 60 parts high-alumina powder and 40 parts copper powder, totaling 100 parts by weight.
[0072] Step 4: Pressing and compacting the billet. The order of powder application is as follows: 7.5 kg / m² of ordinary powder, then 1.5 kg / m² of high-alumina powder, then 3 kg / m² of high-toughness powder, then another 1.5 kg / m² of high-alumina powder, and finally 7.5 kg / m² of ordinary powder. After powder application, the billet is pressed and dried. The coefficient of thermal expansion of the ordinary powder layer is 8.3 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of the high-alumina powder layer is 6.95 × 10⁻⁶. -6 K -1 The coefficient of thermal expansion of the high-toughness powder layer is 10.65 × 10⁻⁶. -6 K -1 The thickness of the (single-layer) ordinary powder layer is 3.8 mm, the thickness of the (single-layer) high-alumina powder layer is 0.75 mm, and the thickness of the high-toughness powder layer is 1.5 mm.
[0073] Step 5: Dry the green body and apply a top glaze to its surface. The mineral composition of the top glaze includes, by mass percentage: 31% potassium feldspar, 20% sodium feldspar, 15% kaolin, 15% silicate sand, 10% zirconium silicate, 2% alumina, 3% calcined talc, and 4% calcined kaolin. The chemical composition of the top glaze includes, by mass percentage: 65.63% SiO2, 18.00% Al2O3, 0.15% Fe2O3, 0.14% TiO2, 0.27% CaO, 1.09% MgO, 3.51% K2O, 3.04% Na2O, 6.37% ZrO2, and a loss on ignition of 1.80%. The top glaze is applied by spraying, with a specific gravity of 1.45 g / cm³. 3 Glazing amount 500 g / m 2 .
[0074] Step 6: Print a regular ink pattern on the surface of the blank after applying the glaze.
[0075] Step 7: Apply a protective glaze to the surface of the blank after inkjet printing the pattern with ordinary ink. The mineral composition of the protective glaze includes, by mass percentage: 15% potassium feldspar, 40% sodium feldspar, 15% kaolin, 3% zinc oxide, 6% calcite, 4% calcined talc, 9% barium carbonate, 3% alumina, and 5% calcined kaolin. The chemical composition of the protective glaze includes, by mass percentage: 52.49% SiO2; 19.86% Al2O3; 1.54% MgO; 3.46% CaO; 7.01% BaO; 2.98% ZnO; 1.96% K2O; 4.36% Na2O; and a loss on ignition of 6.34%. The protective glaze is applied by spraying. The specific gravity of the protective glaze is 1.35 g / cm³. 3 Glazing amount is 280 g / m 2 .
[0076] Step 8: Firing the green body after applying the protective glaze. The kiln firing temperature is 1150℃ (temperature of the measuring ring), and the firing cycle is 55 minutes.
[0077] Referring to the stepped drop height-critical cracking height method, the impact resistance was tested using a falling ball impact tester. A 50-gram steel ball was used in the falling ball impact test. The impact-resistant ceramic tile prepared in this example cracked at a height of 90 cm. Using GB / T14389-1993, the impact toughness test method for engineering ceramics, the impact toughness of the impact-resistant ceramic tile prepared in this example was 3.28 kJ / m. 2 .
Claims
1. A multi-layer oxygen-barrier impact-resistant ceramic tile body based on in-situ copper reinforcement, characterized in that, The blank has a multi-layer structure, including a common powder layer, a high-alumina powder layer, a high-toughness powder layer, another high-alumina powder layer, and a common powder layer arranged sequentially. The chemical composition of the high-alumina powder includes, by mass percentage: SiO2: 50%~60%; Al2O3: 30%~40%; Fe2O3: 0.5%~1.5%; TiO2: 0.1%~0.8%; CaO: 0.1%~0.5%; MgO: 0.2%~1.5%; K2O: 1%~3%; Na2O: 1%~2%; loss on ignition: 3%~8%. The raw material composition of the high-toughness powder includes, based on a total of 100 parts by weight of high-alumina powder and copper powder: 40~70 parts of high-alumina powder and 30~60 parts of copper powder. The thickness ratio of the common powder layer, the high-alumina powder layer, and the high-toughness powder layer is 5~12:1:1~4.
2. The green body for multi-layer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement according to claim 1, characterized in that, The mineral composition of high-alumina powder includes, by mass percentage: 5%~16% sodium sand, 10%~20% potassium aluminum sand, 8%~15% high white potassium sand, 18%~45% clay, 1%~4% bentonite, 1%~4% talc, 20%~40% high alumina stone, and 2%~6% waste porcelain powder.
3. The green body for multi-layer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement according to claim 1, characterized in that, The chemical composition of the common powder includes, by mass percentage: SiO2: 60%~68%; Al2O3: 20%~25%; Fe2O3: 0.4%~1.0%; TiO2: 0.2%~0.4%; CaO: 0.1%~0.6%; MgO: 0.2%~1.2%; K2O: 1.5%~5%; Na2O: 1.5%~4%; Loss on ignition: 3%~8%.
4. The green body for multi-layer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement according to claim 3, characterized in that, The mineral composition of ordinary powder includes, by mass percentage: sodium sand 19%~32%, potassium aluminum sand 15%~30%, high white potassium sand 10%~20%, ball clay 18%~41%, bentonite 1%~4%, talc 1%~4%, high aluminum stone 2%~8%, and waste porcelain powder 1%~6%.
5. The green body for multi-layer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement according to claim 1, characterized in that, The coefficient of thermal expansion of ordinary powder layers is 8.0 × 10⁻⁶ at 40~600℃. -6 K -1 ~ 9.5×10 -6 K -1 The coefficient of thermal expansion of the high-alumina powder layer at 40~600℃ is 6.5×10⁻⁶. -6 K -1 ~ 8.0×10 -6 K -1 The high-toughness powder layer has a coefficient of thermal expansion of 9.2 × 10⁻⁶ at 40–600℃. -6 K -1 ~ 12.8×10 -6 K -1 .
6. The green body for multi-layer oxygen-barrier impact-resistant ceramic bricks based on in-situ copper reinforcement according to claim 1, characterized in that, The thickness of the ordinary powder layer is 3~6 mm, the thickness of the high-alumina powder layer is 0.5~1 mm, and the thickness of the high-toughness powder layer is 1~2 mm.
7. A multi-layer oxygen-barrier impact-resistant ceramic brick based on in-situ copper reinforcement, characterized in that, Includes the green body for multilayer oxygen-barrier impact-resistant ceramic bricks based on copper in-situ reinforcement according to any one of claims 1 to 6.
8. A method for preparing a multi-layer oxygen-barrier impact-resistant ceramic brick based on in-situ copper reinforcement according to claim 7, characterized in that, The preparation method includes the following steps: Step (1) The ordinary powder, high alumina powder, high toughness powder, high alumina powder and ordinary powder are applied in sequence, and then the blank is obtained by pressing. Step (2) Apply a surface glaze to the dried body surface; Step (3) Print a pattern in ordinary ink on the surface of the glazed body by inkjet printing; Step (4) Apply a protective glaze to the surface of the blank after inkjet printing a pattern with ordinary ink; Step (5) Fire the green body after applying the protective glaze to obtain a multi-layer oxygen-barrier impact-resistant ceramic brick based on in-situ copper reinforcement.
9. The preparation method according to claim 8, characterized in that, In step (1), first apply 6-12 kg of ordinary powder per square meter, then apply 1-2 kg of high-alumina powder per square meter, then apply 2-4 kg of high-toughness powder per square meter, then apply 1-2 kg of high-alumina powder per square meter, and finally apply 6-12 kg of ordinary powder per square meter.
10. The preparation method according to claim 8, characterized in that, In step (5), the firing temperature is 1130~1180℃ and the firing cycle is 40~60 minutes.